Assessing lumbar posture variability in individuals with chronic low back pain in daily life - Schömig, Friederike; Bashkuev, Maxim; Reitmaier, Sandra; Fleig, Lena; Pumberger, Matthias; Schmidt, Hendrik (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionInvestigating lumbar spinal posture has become increasingly important for understanding the development and persistence of low back pain (LBP). However, there is a notable lack of studies analyzing changes in lumbar posture variability in individuals with LBP compared with healthy individuals in daily life. This study aims to address this gap by examining whether lumbar posture patterns differ between individuals with and without LBP throughout the day.MethodsA prospective study design was utilized, including individuals with and without chronic LBP. Lumbar postures were continuously measured over a 24-hour period using the Epionics SPINE system.ResultsThe study included 208 (115 females) asymptomatic individuals and 104 (62 females) individuals with LBP. Individuals with LBP exhibited significantly fewer main lumbar postures during the day compared to healthy participants (1.7 vs 1.9 main postures, p = 0.020; r = 0.132). When analyzed by sex, these differences remained statistically significant in males (1.6 vs 1.9 main postures, p = 0.034; r = 0.183) but not in females (1.7 vs 1.8 main postures, p = 0.238; r = 0.089). Age did not significantly influence these results.ConclusionThe observed changes in lumbar spinal posture variability should be taken into account when developing treatment plans for individuals with chronic LBP. Further research is needed to confirm the impact of increased posture variability on pain persistence.